Financial Management to Enhance the Professionalism of Elementary School Teachers - Desi Ratia Citra; Amiruddin Siahaan; Fatkhur Rohman (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Educational financing supports teachers’ professional development in elementary schools. This study analyzes the planning, implementation, supervision, and evaluation of educational financing and its contribution to teacher professionalism at UPTD SD Negeri 015917 Sipaku Area. The study employed a qualitative approach involving the principal, treasurer, and teachers chosen purposively. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using Miles and Huberman’s model. The findings show that the school prepared the RKAS participatively, allocated 10–15% of BOS funds for continuing professional development, distributed the budget according to needs and a rotation system, and conducted supervision through the principal, TPMPS, school supervisor, and ARKAS. Post-training evaluation was conducted for three to four weeks. The financing strengthened teachers’ abilities to prepare teaching modules, implement differentiated instruction, participate in KKG/MGMP, conduct classroom action research, and build collaboration. These findings confirm that participatory, transparent, targeted, and accountable financing can sustainably improve teacher professionalism.